Resolving Marriage Dispensation Cases for Pregnant Women Due to Adultery as Urgent Grounds: An Analysis of Practices in the Simalungun Religious Court - Mulyadi Antori; Sukiati Sukiati; Imam Yazid (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2024)
In 2023, the Simalungun Religious Court adjudicated two cases involving marriage dispensations for pregnant women: Decision Number 26/Pdt.P/2023/PA.Sim and Decision Number 62/Pdt.P/2023/PA.Sim. The outcomes of these cases highlighted a significant divergence, with one ruling in favor of the dispensation request while the other denied it. This study aims to analyze both the Islamic and formal legal perspectives regarding marriage for pregnant women, evaluate scholarly views on marriage dispensations, and conduct a comparative analysis of the judicial considerations influencing these decisions. Employing a normative legal research approach, the findings indicate three key points: First, there exists a significant difference among Islamic scholars concerning the validity of marriages involving women pregnant from adultery; while Imam al-Shafi’i and Imam Abu Hanifah accept such marriages under specific conditions, Imam Malik and Imam Ahmad ibn Hanbal reject them, regardless of the identity of the husband. Second, marriage dispensations for pregnant women are compatible with Islamic law, as endorsed by several scholars. Legally, the framework for marriage dispensations is provided by the Marriage Law and Supreme Court Regulation (PERMA) No. 5 of 2019. Third, Decision Number 26/Pdt.P/2023/PA.Sim, which approved the dispensation, reinforces legal certainty, whereas Decision Number 62/Pdt.P/2023/PA.Sim, which denied it, raises potential issues regarding the predictability of legal outcomes.